Hypoxia: A Double-Edged Sword During Fungal Pathogenesis? - Chung, Hyunjung; Lee, Yong-Hwan (Frontiers in Microbiology, 2020)
Molecular oxygen functions as an electron acceptor for aerobic respiration and a substrate for key metabolisms and cellular processes. Most eukaryotes develop direct or indirect oxygen sensors and reprogram transcriptional and translational metabolisms to adapt to altered oxygen availability under varying oxygen concentrations. Human fungal pathogens manipulate transcriptional levels of genes related to virulence as well as oxygen-dependent metabolisms such as ergosterol homeostasis when they are confronted with oxygen limitation (hypoxia) during infection. Oxygen states in plant tissues also vary depending on site, species, and external environment, potentially providing hypoxia to plant pathogens during infection. In this review, knowledge on the regulation of oxygen sensing and adaptive mechanisms in eukaryotes and nascent understanding of hypoxic responses in plant pathogens are summarized and discussed.